Pergeseran Hukum Kewarisan Islam di Indonesia dengan Pemberian Wasiat Wajibah Kepada Istri yang Non Muslim Berdasarkan Putusan Mahkamah Agung Nomor 16k/Ag/2010 - Maman Suparman (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2023)
The problem of Islamic inheritance law is very broad and complex, because it covers the scope of human life and society, from the problems of unborn children to death, so it is impossible to reveal the whole. In one family, if there are several adherents of different religions, namely some who are Muslims and some who are non-Muslims, of course problems will arise, especially problems involving inheritance if one of the family members dies. Regarding inheritance from different religions, Legal Compilation Islam (KHI) does not explicitly state that religious differences are a barrier to inheritance. According to the Fatwa of the Indonesian Ulema Council in number 2, that the gift of property between people of different religions can only be done by means of a gift, will or gift, however, if the heir during his lifetime does not provide the assets are in the form of bequests, wills or gifts, but the Fatwa does not regulate that heirs of different religions can be given the heir's inheritance by means of a Compulsory Will.